Axonal Neuropathies due to Mutations in Small Heat Shock Proteins: Clinical, Genetic, and Functional Insights into Novel Mutations. Issue 5 (25th February 2017) - Echaniz‐Laguna, Andoni; Geuens, Thomas; Petiot, Philippe; Péréon, Yann; Adriaenssens, Elias; Haidar, Mansour; Capponi, Simona; Maisonobe, Thierry; Fournier, Emmanuel; Dubourg, Odile; Degos, Bertrand; Salachas, François; et al.
Abstract : We report a clinical and genetic study of a cohort of 510 unrelated patients with hereditary axonal neuropathies. In 45 patients we identified mutations in the small heat shock proteins HSPB1 and HSPB8. To understand the consequences of these mutations we performed functional studies of five HSPB1 and three HSPB8 mutations that have not been reported previously. The diverse biological outcomes demonstrate the multifunctional character of small heat shock proteins in health and disease. ABSTRACT: In this study, we describe the phenotypic spectrum of distal hereditary motor neuropathy caused by mutations in the small heat shock proteins HSPB1 and HSPB8 and investigate the functional consequences of newly discovered variants. Among 510 unrelated patients with distal motor neuropathy, we identified mutations in HSPB1 (28 index patients/510; 5.5%) and HSPB8 (four index patients/510; 0.8%) genes. Patients have slowly progressive distal (100%) and proximal (13%) weakness in lower limbs (100%), mild lower limbs sensory involvement (31%), foot deformities (73%), progressive distal upper limb weakness (29%), mildly raised serum creatine kinase levels (100%), and central nervous system involvement (9%). We identified 12 HSPB1 and four HSPB8 mutations, including five and three not previously reported. Transmission was either dominant (78%), recessive (3%), or de novo (19%). Three missense mutations in HSPB1 (Pro7Ser, Gly53Asp, and Gln128Arg) cause hyperphosphorylation of neurofilaments, whereas the C‐terminal mutant Ser187Leu triggers protein aggregation. Two frameshift mutations (Leu58fs and Ala61fs) create a premature stop codon leading to proteasomal degradation. Two mutations in HSPB8 (Lys141Met/Asn) exhibited increased binding to Bag3. We demonstrate that HSPB1 and HSPB8 mutations are a major cause of inherited motor axonal neuropathy. Mutations lead to diverse functional outcomes further demonstrating the pleotropic character of small heat shock proteins.